Exploring the Role of Sociocultural Norms in Shaping Parental Language and Communication Strategies in Sexual Education for Adolescents in Ghana - Quainoo, Michael Asante; Charway, Rosemary; Dogbatse, Felicity Sena (Asia Social Issues, 2025)
Although researchers have widely studied parent-child communication about sex and reproductive health, few have examined the specific language choices parents use during these conversations, especially in a conservative country like Ghana. Using an explanatory sequential mixed-methods design, this study explored how parents use language in discussions with adolescents about sex and reproductive health, and how it affects adolescents’ comfort and understanding. Through an initial survey of 170 undergraduate students aged 17–27 at the University of Cape Coast, and a semi-structured interview with seven purposively selected participants, we found that, many adolescents face significant barriers in initiating open conversations about sex with their parents. This is largely due to the absence of a communicatively open environment at home. Additionally, parents frequently relied on euphemisms, pet names, and metaphors to reference sexual and reproductive topics, which often limited clarity and hindered effective knowledge transmission. This study highlights the need for more direct and developmentally appropriate language in parent-adolescent communication to support adolescents’ sexual and reproductive well-being.